Research on Strategies for Digital Asset Management in Chinese Universities - Zhang, Lijuan (International Journal of Global Economics and Management, 2025)
At present, in the process of informatization in universities, the in-depth application of high-quality data resources has become a core driving force of educational reform. Digital assets have become an important asset for universities across China. However, there are still issues in the management of digital assets in Chinese universities, such as the lack of unified standards and regulations, as well as relatively fragmented management. In response to these problems, this paper proposes strategic suggestions from several perspectives, including digital asset management policies or systems, digital asset sharing mechanisms, digital asset information security mechanisms, and the application of digital assets.